Exploring the Enhanced Performance of a Static Synchronous Compensator with a Super-Capacitor in Power Networks - Vaidya, P.; Chandrakar, V. K. (Engineering, Technology & Applied Science Research, 2022)
The use of a super-capacitor as a storage device integrated with a Voltage source converter-based shunt-connected Static Synchronous Compensator (STATCOM) is proposed for improving the STATCOM performance during sudden large disturbances in a power network. The super-capacitor was applied across the STATCOM capacitor during the disturbance condition. MATLAB simulations were carried out for the verification of a secondary function of the STATCOM like oscillation damping, transient stability improvement, and security of the power network with the storage device. The validation of the proposed super-capacitor was carried out in MATLAB.